2007
DOI: 10.1111/j.1744-7348.2007.00137.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of white clover as an alternative to nitrogen fertiliser for dairy pastures in nitrate vulnerable zones in the UK: productivity, environmental impact and economic considerations

Abstract: Perennial ryegrass and perennial ryegrass/white clover permanent dairy pastures are compared with respect to productivity, environmental impact and financial costs in nitrate vulnerable zones (NVZ) in the UK. With appropriate management, and utilisation of recommended perennial ryegrass and white clover cultivars, white clover is likely to stabilise at around 20% of total dry matter production in a mixed pasture. Plant dry matter production and milk production from a perennial ryegrass/white clover pasture are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 74 publications
3
90
0
2
Order By: Relevance
“…, similar to that observed in the UK (Parsons et al 1991;Andrews et al 2007) and NZ (Woodfield and Clark 2009), although Jarvis (1993) suggested that in the UK, dairy pastures were typically much lower in both clover content (<10%) and the amount of N 2 fixed (10 kg ha -1 year -1 ). These low clover contents are likely to be suboptimal in terms of dairy production (Woodfield and Clark 2009) as well as N 2 fixation and thus efforts to increase N 2 fixation should be rewarded with increased milk production efficiency.…”
Section: The Achilles Heel: Low White Clover Content Of Pasturessupporting
confidence: 72%
See 2 more Smart Citations
“…, similar to that observed in the UK (Parsons et al 1991;Andrews et al 2007) and NZ (Woodfield and Clark 2009), although Jarvis (1993) suggested that in the UK, dairy pastures were typically much lower in both clover content (<10%) and the amount of N 2 fixed (10 kg ha -1 year -1 ). These low clover contents are likely to be suboptimal in terms of dairy production (Woodfield and Clark 2009) as well as N 2 fixation and thus efforts to increase N 2 fixation should be rewarded with increased milk production efficiency.…”
Section: The Achilles Heel: Low White Clover Content Of Pasturessupporting
confidence: 72%
“…While this is beyond the scope of the present review we can briefly consider some of the issues feeding into and out of legume N in dairy farming systems. More thorough environmental analyses of dairy farming systems can be found in a recent volume (de Klein et al 2008;Kleinman and Soder 2008;Nash and Barlow 2008) and a range of other relevant articles (Ridley et al 2004;Andrews et al 2007;Ledgard et al 2009;Woodfield and Clark 2009).…”
Section: Environmental Costs and Benefits Of N 2 Fixationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these strategies it has been investigated a reduced use of synthetic nitrogen fertilizers, splitting their annual application rate, use of slow release fertilizer (Adams et al, 2013), adjustment of supply the current demand, use of urease and/or nitrification inhibitors (Zaman et al, 2009), application of organic fertilizers, increased intervals between defoliation (Kennedy et al, 2006), and use of plants can take up and use nitrogen captured from soil. All these practices comply with the objective of increasing the efficiency of nitrogen use, reduce air pollution and Seasonal variation of the productivity and quality of permanent pastures in Adisols of temperate regions increase the protein content of the plants (Andrews et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Ground water contamination: Nitrate (NO3 -) leaching losses from soil into the water bodies are not only the loss of soil fertility but have a tremendous effect on environment and human health (Goulding et al, 2008). Drinking of water and consumption of vegetables contaminated with NO3 -causing intestinal disease and it is associated with stomach cancer, as well (Andrews et al, 2007). Animal manures and commercial fertilizers have excess of nitrogen which cause many events of nitrate contamination in intensive agriculture especially in greenhouse vegetable production (Zhang et al, 1996;Li et al, 2002;Song et al, 2009).…”
Section: Nitrogen Losses Associated With Nitrification and Environmenmentioning
confidence: 99%